A review on protection of boiler tube steels with thermal spray coatings from hot corrosion. (2022) - Singh, Sukhjinder; Goyal, Khushdeep; Bhatia, Rakesh
Abstract: The conventional steels and their alloys are not able to withstand high temperature corrosion in boilers of thermal power plants. The problem of hot corrosion has become more severe issue due to increasing operating temperatures of boilers. In recent past, many researchers have tried to reduce hot corrosion of boiler steels by surface coatings. Different thermal spray coating techniques have been developed to spray different types of coatings on boiler steels. These coating techniques have been proved to enhance corrosion resistance of boiler steels and to increase their performance at high operating temperatures, which subsequently have increased their life span. The advancements and developments in thermal spraying techniques have resulted in development of surface coatings with highly excellent corrosion resistance properties. This paper reviews the performance, developments and applications of thermal spray coatings for high temperature corrosion resistance.